(untitled) (Palíndromo, 2026)
This article presents, through the Transchimerology methodology and contributions from Performance Studies and Neomaterialist Feminisms, the concepts of museum of performance, museum as performance, and performative museum. It aims to conceive, based on themes such as matter, time, and archive, another performative museum notion: the museum-performance. To this purpose, it narrates how MUTHA destabilizes binaries such as subject/object, archivist/archive, constituting itself as a performance and as a museum-work-of-art.